Effects of Farmers-Herders Skirmish on Nigeria National Security: An Appraisal - Bello , Muhammad (Kashere Journal of Politics and International Relations, 2025)
Farmers-herders scrimmage is of late pervasive across the shores of sub –Sahara Africa. In Nigeria, the development has rapidly transcend the boundaries of the nation’s geopolitical zones and swiftly transforming dynamically and tactically involving its inhabitants as hardly would any group be off hook the act of pastoralism. This paper set out to evaluate farmer’s herder’s conflict in Nigeria and its challenges to national security. Details for the analysis were gather from primary and secondary sources through the use of documentary research technique and focus group discussion with knowledgeable on the subject matter, the literature were judiciously scrutinize using the descriptive methodology. The study revealed that while cases of farmer’s herders clash cannot be completely contained, the development is now taking a new dimension with the infusion of politicization, ethnicity and religious posture